Design of a wide-particle-size-range aerodynamic injection system with a new pre-focus structure - J. Huang; L. Li; X. Li; Z. Huang; Z. Cheng (Atmospheric Measurement Techniques, 2025)
A new aerodynamic injection system has been designed for a wide particle size range, combining a new pre-focus structure, a smaller buffer chamber, and a five-stage lens. Compared with previous injection systems, the new design adds virtual impactors and pre-focus structures, while reducing the overall volume by 90 %. The newly developed pre-focus structure effectively addresses the challenges associated with the focusing and transmission of large particles, significantly reducing the beam width and dispersion angle of particles exiting the critical hole, thus preventing the buffer chamber from becoming excessively large. Furthermore, the focusing capability and transmission efficiency for large particles have been significantly enhanced, with the transmission range expanded to encompass particles from 100 nm to 10 µm. Numerical simulations demonstrate that the injection system can transmit particles within the 1 to 9 µm range with an efficiency exceeding 90 %. Additionally, the standard micro-sphere experiment verified the good consistency between the performance of the injection system and the simulation results. In the testing of standard dust, the wide-range particle size distribution obtained using the new injection system is highly consistent with the aerodynamic particle sizer (APS). In summary, this new design has ultra-high transmission efficiency while reducing volume, demonstrating the miniaturization potential of the single-particle aerosol mass spectrometer when detecting particles with a wide particle size range.